KOMPOSISI JENIS UDANG AIR TAWAR DI SUNGAI BATAMBEAN, PULAU LABOBO, BANGGAI LAUT, SULAWESI TENGAH, INDONESIA - Rahayu, Puji; Annawaty, Annawaty (Natural Science: Journal of Science and Technology, 2019)
Labobo isle is one of the satellite isle located around the mainland of Sulawesi Island. This study aims to determine the species composition of freshwater shrimp in the Batambean Stream located on Labobo Island, Banggai Laut, Central Sulawesi, Indonesia. A purposive sampling method based on the habitat of freshwater shrimps was applied to collect the shrimps. Measurement of abiotic environmental factors is carried out before samples collection. Furthermore, freshwater shrimp are collected using tray net and hand net. Collected specimens were preserved in alcohol 96%. The specimen wasidentified at the Laboratory of Animal Biosystematics and Evolution, Department of Biology, Faculty of Sciences, Tadulako University. The composition of freshwater shrimp species in the Batambean Stream consists of four species, namely Macrobrachium equidens, M. australe, and M. latidactylus and Caridina gracilipes. The first three species belong to the family Palaemonidae while the latter species is a member of the family Atyidae. The brief description and conservation status of each species  were also provided